ECE Educator Training: How to Develop Literacy and Environment Education for Children? - Titi Chandrawati; Siti Aisyah (Jurnal Pendidikan Usia Dini, 2022)
Loving the environment is a character that must be instilled in children from an early age. This study aims to describe how efforts to instil love for the environment in preschool. This research uses a collaboration action research method with the intervention of providing information and motivation about the importance of environmental education for ECE educators. The participants were the ECE community represented by eleven ECE teachers in the Tangerang, Sawangan Bogor, Medan, and Batam areas. Data collection was carried out by focus group discussions and interviews as well as the delivery of information related to learning and environmental literacy for children through online meetings. Content analysis was used to interpret the data in this study. The findings of this study indicate that the provision of information and motivation to eleven ECE teachers can make the eleven teachers form the spirit and knowledge of teachers to develop learning and teaching environmental literacy in early childhood classes. The teachers are also trying to green the school environment by planting trees and making various learning activities with the children to get to know and love the environment better.Keywords:  ECE educators training, environmental literacy, environmental educationReferences:Bryman, A. (2021). Social Research Methods. Oxford University Press. https://books.google.co.id/books?id=kDZwzgEACAAJBurdette, H. L., & Whitaker, R. C. (2005). Resurrecting Free Play in Young Children: Looking Beyond Fitness and Fatness to Attention, Affiliation, and Affect. Archives of Pediatrics & Adolescent Medicine, 159(1), 46–50. https://doi.org/10.1001/archpedi.159.1.46Chu, H., Lee, E. A., Ryung Ko, H., Hee Shin, D., Nam Lee, M., Mee Min, B., & Hee Kang, K. (2007). Korean Year 3 Children’s Environmental Literacy: A prerequisite for a Korean environmental education curriculum. International Journal of Science Education, 29(6), 731–746. https://doi.org/10.1080/09500690600823532Corraliza, J., Universidad Autónoma de Madrid., Collado, S., & Universidad de Zaragoza. (2019). Ecological Awareness and Children’s Environmental Experience. Papeles Del Psicólogo - Psychologist Papers, 40(2). https://doi.org/10.23923/pap.psicol2019.2896Dada, D. O., Eames, C., & Calder, N. (2017). Impact of Environmental Education on Beginning Preservice Teachers’ Environmental Literacy. Australian Journal of Environmental Education, 33(3), 201–222. Cambridge Core. https://doi.org/10.1017/aee.2017.27Denzin, N. K., & Lincoln, Y. S. (2012). Collecting and Interpreting Qualitative Materials. SAGE Publications. https://books.google.me/books?id=5Z8gAQAAQBAJDisinger, J. F., & Roth, C. E. (1992). Environmental education research news. Environmentalist, 12(3), 165–168. https://doi.org/10.1007/BF01267599Ernst, J., & Burcak, F. (2019). Young Children’s Contributions to Sustainability: The Influence of Nature Play on Curiosity, Executive Function Skills, Creative Thinking, and Resilience. Sustainability, 11(15). https://doi.org/10.3390/su11154212Eugenio-Gozalbo, M., Aragón, L., & Ortega-Cubero, I. (2020). Gardens as Science Learning Contexts Across Educational Stages: Learning Assessment Based on Students’ Graphic Representations. Frontiers in Psychology, 11. https://www.frontiersin.org/articles/10.3389/fpsyg.2020.02226Evans, G. W., Otto, S., & Kaiser, F. G. (2018). Childhood Origins of Young Adult Environmental Behavior. Psychological Science, 29(5), 679–687. https://doi.org/10.1177/0956797617741894Ewert, A., Place, G., & Sibthorp, Ji. (2005). Early-Life Outdoor Experiences and an Individual’s Environmental Attitudes. Leisure Sciences, 27(3), 225–239. https://doi.org/10.1080/01490400590930853Friedman, S., Masterson, M. L., Wright, B. L., Bredekamp, S., & Willer, B. (2021). Developmentally Appropriate Practice in Early Childhood Programs Serving Children from Birth Through Age 8, Fourth Edition (Fully Revised and Updated). National Association for the Education of Young Children. https://books.google.co.id/books?id=Kb-vzQEACAAJGifford, R., & Nilsson, A. (2014). Personal and social factors that influence pro-environmental concern and behaviour: A review. International Journal of Psychology, 49(3), 141–157. https://doi.org/10.1002/ijop.12034Jørgensen, K.-A. (2016). Bringing the jellyfish home: Environmental consciousness and ‘sense of wonder’ in young children’s encounters with natural landscapes and places. Environmental Education Research, 22(8), 1139–1157. https://doi.org/10.1080/13504622.2015.1068277Kaiser, F. G., Brügger, A., Hartig, T., Bogner, F. X., & Gutscher, H. (2014). Appreciation of nature and appreciation of environmental protection: How stable are these attitudes and which comes first? European Review of Applied Psychology-Revue Europeenne De Psychologie Appliquee, 64, 269–277.Kaya, V., & Elster, D. (2019). A Critical Consideration of Environmental Literacy: Concepts, Contexts, and Competencies. Sustainability, 11(6), 1581. https://doi.org/10.3390/su11061581Kidman, G., & Casinader, N. (2019). Developing Teachers’ Environmental Literacy through Inquiry-based Practices. EURASIA Journal of Mathematics, Science and Technology Education, 15(6). https://doi.org/10.29333/ejmste/103065Kim, G., Vaswani, R. T., Kang, W., Nam, M., & Lee, D. (2017). Enhancing Ecoliteracy through Traditional Ecological Knowledge in Proverbs. Sustainability, 9(7). https://doi.org/10.3390/su9071182Larimore, R. (2016). Defining Nature-Based Preschools. The International Journal of Early Childhood Environmental Education, 4(1), 5.Lincoln, Y. S., Guba, E. G., & Publishing, S. (1985). Naturalistic Inquiry. SAGE Publications. https://books.google.co.id/books?id=2oA9aWlNeooCLópez-Alcarria, A., Gutiérrez-Pérez, J., & Poza-Vilches, F. (2014). Preschool Education Professionals as Mediators of Environmental Health Education. 6th International Conference on Intercultural Education “Education and Health: From a Transcultural Perspective", 132, 639–646. https://doi.org/10.1016/j.sbspro.2014.04.366Miles, M. B., Huberman, A. M., & Saldaña, J. (2014). Qualitative data analysis: A methods sourcebook (Third edition). SAGE Publications, Inc.Mills, G. E. (2011). Action Research: A Guide for the Teacher Researcher. Pearson. https://books.google.co.id/books?id=-d1XAAAAYAAJOlgan, R., & Kahri̇Man-Öztürk, D. (2011). An Investigation in the Playgrounds of Public and Private Preschools in Ankara. Education and Science, 36(161), 13.Otto, S., Evans, G. W., Moon, M. J., & Kaiser, F. G. (2019). The development of children’s environmental attitude and behavior. Global Environmental Change, 58, 101947. https://doi.org/10.1016/j.gloenvcha.2019.101947Otto, S., Kaiser, F. G., & Arnold, O. (2014). The Critical Challenge of Climate Change for Psychology. European Psychologist, 19(2), 96–106. https://doi.org/10.1027/1016-9040/a000182Pe’er, S., Goldman, D., & Yavetz, B. (2007). Environmental Literacy in Teacher Training: Attitudes, Knowledge, and Environmental Behavior of Beginning Students. The Journal of Environmental Education, 39(1), 45–59. https://doi.org/10.3200/JOEE.39.1.45-59Phillipson-Mower, T., & Adams, A. D. (2010). Environmental Education Service-Learning in Science Teacher Education. In A. M. Bodzin, B. Shiner Klein, & S. Weaver (Eds.), The Inclusion of Environmental Education in Science Teacher Education (pp. 65–79). Springer Netherlands. https://doi.org/10.1007/978-90-481-9222-9_5Rosa, C. D., Profice, C. C., & Collado, S. (2018). Nature Experiences and Adults’ Self-Reported Pro-environmental Behaviors: The Role of Connectedness to Nature and Childhood Nature Experiences. Frontiers in Psychology, 9. https://www.frontiersin.org/articles/10.3389/fpsyg.2018.01055Roth, C. E. (1992). Environmental Literacy: Its Roots, Evolution and Directions in the 1990s. ERIC/CSMEE Publications. https://books.google.co.id/books?id=8ZA6HQAACAAJSchutte, A. R., Torquati, J. C., & Beattie, H. L. (2017). Impact of Urban Nature on Executive Functioning in Early and Middle Childhood. Environment and Behavior, 49(1), 3–30. https://doi.org/10.1177/0013916515603095Shallcross, T., O’Loan, K., & Hui, D. (2000). Developing a School Focused Approach to Continuing Professional Development in Sustainability Education. Environmental Education Research, 6(4), 363–382. https://doi.org/10.1080/713664694Spano, G., D’Este, M., Giannico, V., Carrus, G., Elia, M., Lafortezza, R., Panno, A., & Sanesi, G. (2020). Are Community Gardening and Horticultural Interventions Beneficial for Psychosocial Well-Being? A Meta-Analysis. International Journal of Environmental Research and Public Health, 17(10). https://doi.org/10.3390/ijerph17103584Ulrich Müller, Viviene A. Temple, Beverly Smith, Kimberly Kerns, Kayla Ten Eycke, Jeff Crane, & John Sheehan. (2017). Effects of Nature Kindergarten Attendance on Children’s Functioning. Children, Youth and Environments, 27(2), 47–69. JSTOR. https://doi.org/10.7721/chilyoutenvi.27.2.0047Veisi, H., Lacy, M., Mafakheri, S., & Razaghi, F. (2019). Assessing environmental literacy of university students: A case study of Shahid Beheshti University in Iran. Applied Environmental Education & Communication, 18(1), 25–42. https://doi.org/10.1080/1533015X.2018.1431163Wals, A. E. J., & Benavot, A. (2017). Can we meet the sustainability challenges? The role of education and lifelong learning. European Journal of Education, 52(4), 404–413. https://doi.org/10.1111/ejed.12250Wilson, R. A. (1996). Environmental Education Programs for Preschool Children. The Journal of Environmental Education, 27(4), 28–33. https://doi.org/10.1080/00958964.1996.9941473